Establishing a PBL STEM Framework for Pre-Service Teachers - Lisa N. Pitot; Maggie Lee McHugh; Jennifer Kosiak (MDPI AG, 2024)
Research into pre-service teachers' (PSTs) ability to develop meaningful interdisciplinary, project-based curricula is lacking; at the same time, many young adolescents fail to see the connections between their schoolwork and the real world. As such, there is a need for new methods to prepare elementary and middle school teachers' abilities to integrate mathematics and science through authentic content. This article will examine how elementary and middle PSTs collaborated across their mathematics and science methods courses to design project-based learning (PBL) unit plans that integrate social justice and global awareness in a STEM context. The content analysis of 25 distinct PBL unit plans documented the levels at which PSTs could incorporate practical PBL design elements into their projects, integrate robust mathematical content, and identify connections to social justice and global awareness. Through this analysis, we will share the successes and challenges faced in guiding PSTs to create PBL STEM units and present a series of next steps that could be taken to further this cross-curricular endeavor.